The criminalization of the state in Africa - Bayart, Jean Francois (Oxford J.Currey, 1999)
The growth of fraud and smuggling on a major scale, the plundering of natural resources, the privatisation of state institutions, the development of an economy of plunder, the growth of private armies―all of these features of public life in Africa suggest that the state itself is becoming a vehicle for organised criminal activity. The three authors propose criteria for gauging the criminalisation of African states and present a novel prognosis.
Bibliography note: Includes bibliographical references and index.
Keywords: Political corruption -- Africa; Political crimes and offenses -- Africa